The Gestalt Whitehead - Desmet, Ronny (Process studies, 2015)
The aim of the first part of this article is to highlight some of the historical roots of the affinities of Whitehead’s philosophy with Gestalt psychology by identifying a number of physicists as well as philosopher-psychologists playing a relevant role in both the genesis of Whitehead’s thought and that of Gestalt psychology. The article goes beyond identifying Faraday and Maxwell as well as James and Bergson as relevant in this respect. It also focuses on others who have influenced Whitehead: Lorentz as well as Lotze and Brentano, Ward and Stout. The aim of the second part of this article is to introduce three of Whitehead’s key ideas by means of a number of simple Gestalt experiments: his idea of what mathematics is all about, his idea of what is wrong with Einstein’s interpretation of special and general relativity, and his idea of the role of recognition in the subjective form of feeling.